Comparison of Lethal and Nonlethal Sampling Methods for the Detection of Largemouth Bass Virus (LMBV) from Largemouth Bass in the Upper Mississippi River. Issue 3 (24th July 2018) - Leis, Eric; McCann, Rebekah; Standish, Isaac; Bestul, Anna; Odom, Torri; Finnerty, Casey; Bennie, Barb
Abstract: Traditional methodologies to identify fish pathogens require euthanasia before the collection of tissue samples. While these methods are standardized and proven, there are instances where nonlethal alternatives would be preferred. Despite the need to develop nonlethal sampling techniques, few publications have focused on them and even fewer have used these approaches to identify viruses from infections occurring in wild fish populations. In this study, we compared the ability of nonlethal sampling techniques with traditional methods for the detection of Largemouth Bass virus (LMBV) from a wild population of Largemouth Bass Micropterus salmoides from the upper Mississippi River. Largemouth bass virus was isolated from 30% of the Largemouth Bass sampled using traditional methods where tissue samples were inoculated on Bluegill fry (BF‐2) cells. Furthermore, when using tissue cell culture to isolate LMBV, there was no significant difference observed in the overall proportion that was positive between the mucus samples and the kidney and spleen samples. Mucus swabs analyzed with molecular methods (conventional PCR and quantitative PCR) were more sensitive than traditional tissue cell culture‐based methods as they detected LMBV from >70% of the samples; limitations to these methods (i.e., carryover contamination) were also identified. The results of this study suggest that nonlethal sampling may be a useful option for detecting LMBV from fish populations.